Micro Small and Medium Enterprises and Socioeconomic Welfare in Bayah Barat Village: Usaha Mikro Kecil dan Menengah dan Kesejahteraan Sosial Ekonomi Desa Bayah Barat - Zaky, Ahmad; Padillah, Teja Amhar; Saputra, Dimas; Oktavia, Salwa; Akhdam, Nasywa Fawwaz; Delfiza, Yandri; Daeng, Amalina Adani Putri; Pidreansyah, Syarifah Khansa (Indonesian Journal of Innovation Studies, 2026)
General Background: Micro, Small, and Medium Enterprises are widely recognized as a fundamental pillar of rural economic systems in Indonesia, particularly in supporting household livelihoods and local economic circulation. Specific Background: In Bayah Barat Village, Lebak Regency, MSMEs based on banana processing and home industries represent dominant community economic activities rooted in local resources and traditional knowledge. Knowledge Gap: Despite their persistence, limited empirical studies have documented how these MSMEs contribute to socio-economic welfare while simultaneously facing constraints related to capital access, marketing reach, and digital literacy at the village level. Aims: This study aims to analyze the contribution of MSMEs to socio-economic welfare in Bayah Barat Village and to formulate a digital-based strengthening strategy grounded in community participation. Results: Using a Participatory Rural Appraisal approach, the findings indicate that MSMEs contribute to employment absorption, household income generation, and local economic strengthening, while encountering structural challenges including limited financing, raw material stability, and conventional marketing practices. Novelty: The study highlights a community-based perspective that integrates traditional production systems with participatory analysis to identify digital marketing and alternative financing pathways. Implications: These findings imply the need for inclusive financing access, entrepreneurial capacity building, digital literacy improvement, product standardization, and strengthened village institutional collaboration to support sustainable community-based MSME development. Highlights • MSMEs support employment and household income through banana-based home industries• Participatory Rural Appraisal reveals capital and marketing constraints at village level• Community-based digital strategies align local resources with economic sustainability Keywords Micro Small And Medium Enterprises; Socioeconomic Welfare; Participatory Rural Appraisal; Digital Marketing; Bayah Barat Village